2013
DOI: 10.1016/j.jssc.2012.08.009
|View full text |Cite
|
Sign up to set email alerts
|

High temperature structural and magnetic properties of cobalt nanorods

Abstract: International audienceWe present in this paper the structural and magnetic properties of high aspect ratio Co nanoparticles (~10) at high temperatures (up to 623 K) using in-situ X ray diffraction (XRD) and SQUID characterizations. We show that the anisotropic shapes, the structural and texture properties are preserved up to 500 K. The coercivity can be modelled by µ0HC = 2(KMC + Kshape)/MS with KMC the magnetocrystalline anisotropy constant, Kshape the shape anisotropy constant and MS the saturation magnetiza… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
41
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 46 publications
(44 citation statements)
references
References 33 publications
3
41
0
Order By: Relevance
“…Figure 1b shows 3 hysteresis loops for the same structure calculated by the macro spin, μmag and oHmag method. The results are in good agreement with experimental data [1].…”
Section: Packed Nanorodssupporting
confidence: 90%
See 1 more Smart Citation
“…Figure 1b shows 3 hysteresis loops for the same structure calculated by the macro spin, μmag and oHmag method. The results are in good agreement with experimental data [1].…”
Section: Packed Nanorodssupporting
confidence: 90%
“…A densely packed structure of high-aspect-ratio (1:5 -1:10) cobalt nanorods exploits both sources of anisotropy and experiments showed that these structures maintain high coercivity values at high temperatures, because the shape anisotropy is temperature-independent [1].…”
Section: Introductionmentioning
confidence: 99%
“…Due to the absence of defects and to their mono--crystalline state, experimental coercivity can reach values larger than 0.5 T at room temperature. We showed in previous work that half of the observed coercivity could be accounted for by the magneto--crystalline anisotropy (Maurer 2007 andAit--Atmane 2013). The remaining part can be attributed to the shape anisotropy contribution.…”
Section: Introductionmentioning
confidence: 75%
“…The first term is expected to be temperature dependent while the second is almost constant as function of temperature (in the range 20-200 K) and only differs for different morphologies (author?) [32]. The effective anisotropy acting then on a single nanowire can be written as the sum of the magnetocrystalline and shape contributions if both are aligned with the length of the nanowire.…”
Section: Nanowire Shape and Length Effectsmentioning
confidence: 99%